Biodiesel Production from Waste Cooking Oil Using Hydrodinamic Cavitation - Supardan, Muhammad Dani; Satriana, Satriana; Mahlinda, Mahlinda (Makara Journal of Technology, 2012)
The aim of this research was to study biodiesel production from low cost feedstock of waste cooking oil (WCO) using hydrodynamic cavitation apparatus. A two-step processes esterification process and transesterification process using hydrodynamic cavitation for the production of biodiesel from WCO is presented. The first step is acid-catalyzed esterification process for reducing free fatty acid (FFA) content of WCO and followed by base-catalyzed transesterification process for converting WCO to biodiesel as the second step. The result of esterification process with methanol to oil molar ratio of 5 and temperature of 60 oC showed that the initial acid value of WCO of 3.9 mg KOH/g can be decreased to 1.81 mg KOH/g in 120 minutes. The highest yield of biodiesel in transesterification process of 89.4% obtained at reaction time of 150 minutes with methanol to oil molar ratio of 6. The biodiesel produced in the experiment was analyzed by gas chromatography-mass spectrometry (GC-MS), which showed that it mainly contained five fatty acid methyl esters. In addition, the properties of biodiesel showed that all of the fuel properties met the Indonesian National Standard (INS) No. 04-7182-2006 for biodiesel.